A sociology of globalization (2007)
In its introduction, the text presents the basis for a sociology of globalization at affirming that such a phenomenon is comprehensible not only in terms of interdependency and formation of exclusively global institutions but in regard to something within what is national. After overcoming a methodological nationalism it becomes possible to approach a growing number of cases of localization of what is global and others of denationalization of what is national which, meanwhile, opens a wide range of research possibilities in social sciences. Then, a study of global cities as a convenient space to test theoretical assumptions of such a sociology is undertaken since, in those cities, a new transnational geography serving as a space for new transnational politics emerges.